Prevalence of Porcine Cysticercosis in Four States of North East India - Barua, Acheenta Gohain; Raj, Himangshu; Goswami, Chandrani; Sonowal , Dharitree; Rajkhowa, Uttam (International Journal of Livestock Research, 2018)
Porcine cysticercosis is an important parasitic zoonotic disease in North East India, where pork is consumed by 80-85% of the population as an important form of dietary protein. It is endemic in these areas but minimal data has been reported concerning prevalence of porcine cysticercosis. The present work was undertaken to study the prevalence of porcine cysticercosis in the three North Eastern states of Assam, Meghalaya and Arunachal Pradesh. Different pork markets of different districts of the states were selected randomly from these three states. Postmortem inspection was carried out for examining cyst-like nodules. Blood samples were collected and performed ELISA for detection of circulatory taenia spp. antibodies. Overall prevalence of porcine cysticercosis in these states of NE India was recorded 0.92 %. Highest prevalence was recorded in Meghalaya (1.73 %) followed by Arunachal Pradesh (1.39 %) and Assam (0.68 %). Sero-prevalence of porcine cysticercosis in these four states was recorded 2.72 % comprising 2.13 %, 5.37 %, 3.18 % and 1.82 % in Assam, Meghalaya, Arunachal Pradesh and Mizoram respectively. Data obtained in this study suggested presence of porcine cysticercosis in these states of North East India. These results indicate urgent necessity to implement appropriate control measures for Taenia solium in the study areas.